Pengaruh Pemberian Beberapa Jenis Pupuk Organik Cair Terhadap Pertumbuhan Bibit Tanaman Kakao - Selmi Yohana Stefanie; Iwan Billy Wally (Jurnal Indonesia Sosial Teknologi, 2022)
The Effect of Giving Several Types of Liquid Organic Fertilizers on the Growth of Cocoa (Theobroma cacao L) Seedlings”. The growth of cacao seedlings is influenced by many factors. One very important factor, namely the availability of nutrients, the availability of nutrients for the growth and development of cocoa seeds can be increased by adding nutrients (fertilizing). Liquid organic fertilizer (POC) is available more quickly and is easily absorbed by plant roots. The purpose of this study was to determine the effect of the application of several types of liquid organic fertilizer and the right type of liquid organic fertilizer on the growth of cacao (Theobroma cacao L.) seedlings. This research was carried out at the Green House of the Agrotechnology Study Program, Faculty of Agriculture, Health and Marine Affairs, Ottow Geissler University, Papua and was carried out for 3 months, from March to May 2020. This study used a completely randomized design (CRD) consisting of 4 treatments and repeated 4 times. , so that 16 experimental units were obtained. The treatments consisted of Control (without fertilizer), POC Gamal, POC Lamtoro and POC Banana Peel. Observation variables were plant height (cm), number of leaves (strands), leaf width (cm) and leaf length (cm). The resulting data were analyzed by ANOVA at the 95% confidence level, if the treatment had a significant effect, then continued with the BNJ test. The results showed that the treatment that showed the best observed variables for plant height, number of leaves, leaf width and leaf length was liquid organic fertilizer of lamtoro leaves.